Near-Zero Refractive Indices and Collimation Effects in Anisotropic Photonic Crystals with Rectangular Lattices - Saeid Jamilan; Muhammad Danyal; Elena Semouchkina (Fundamental Research and Application of Physical Science Vol. 9, 2023)
The objective of this work is to design highly anisotropic 2D photonic crystals (PhCs) with near-zero refractive indices (NZRIs). We demonstrate that PhCs, composed of dielectric rods and organized in rectangular lattices can support unidirectional wave propagation with NZRIs along short sides of unit cells. Divergent waves that are incident are collimated as a result of complete suppression of wave propagation along the orthogonal direction. We used MPB and COMSOL software packages for simulating the dispersion diagrams, S21 transmission spectra, and wave patterns. The results show that the observed collimation effect is correlated with flat equi-frequency contours (EFCs) of PhCs, while operating frequency corresponds to the lower edge of the 2nd transmission band of the crystal. We have recorded wave patterns beyond PhC fragment designed for operation in the microwave range as experimental confirmation of the computational results. Fabricated samples were irradiated by divergent TM polarized electromagnetic waves and were made up of ceramic dielectric rods with mm-size diameters. Obtained results extend perspectives of low-loss artificial anisotropic media with NZRI properties for microwave and photonic applications. Collimators can have many potential applications in electromagnetics and photonics, such as enhancing the gain and directionality of antennas’ radiation patterns and connecting waveguides with different widths.